Pelatihan digital marketing melalui aplikasi TikTok untuk pelajar di Desa Rogoselo, Kabupaten Pekalongan - Imam Prayogo Pujiono; Moh. Sugeng Solehuddin; Arditya Prayogi; Nur Azizah; Nurul Hikmah Sofyan; Dicky Anggriawan Nugroho (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of information and communication technology in the digital era has made social media platforms like TikTok an effective tool for product marketing. However, in Rogoselo Village, Pekalongan Regency, this potential has not been optimally utilized due to three main problems: low digital literacy among students, limited access to digital marketing information, and the absence of training programs that guide the use of TikTok for productive purposes. Therefore, this community service activity was designed to improve students' understanding and skills in utilizing TikTok as a digital marketing tool to promote local potential. The training was conducted using a combination of presentation and practical methods. Presentation was used to convey theoretical material, while the practical method was used to practice creating TikTok content to promote the participants' products. The training results showed a significant increase in skills: out of 18 participants, the number who answered “Yes” increased by about 10 on average (ranging from 10 to 11 across the five evaluation items), indicating improved understanding and ability to use TikTok for digital marketing purposes. Challenges in the training, such as limited internet access, were overcome by providing portable hotspots. The conclusion of this activity confirmed that the training successfully improved participants' digital literacy and technical skills and opened up opportunities for developing a digital-based creative economy in Rogoselo Village.